Pengaruh Disiplin Kerja Kepala Sekolah dan Motivasi Terhadap Kinerja Guru Sekolah Dasar Negeri - Yulia Yulia; Nur Ahyani; Ratu Wardarita (LPPM Universitas Trunojoyo Madura, 2021)
This research aimed to study and to test the effect of the principal work discipline (variable X1) on teacher performance (variable Y), the effect of the work motivation (variable X2) on teacher performance (variable Y) and the effect of the principal's work discipline (variable X1) and motivation work (variable X2) together on the performance of teachers (variable Y). The method used of this research was survey research design. Based on the results of the data analysis that had been carried out the influence of the principal discipline variable and work motivation variable on the teacher performance variable was 98.3%, this value implied that the principal of the discipline variable and work motivation variable jointly affect of the teacher's performance variable by 98.3%, while the remains was influenced by variables that were not examined. These results indicated that there were an influence of the principal's work discipline variable and work motivation variable on the teacher's performance variable, both individually or together.